Multi-species and multi-tissue methylation clocks for age estimation in toothed whales and dolphins - Todd R. Robeck (Nature Portfolio, 2021)
Todd Robeck and Zhe Fei et al. use DNA methylation profiling to develop an epigenetic clock to measure age in odontocete species, including toothed whales and dolphins. The clocks were highly accurate and represent a valuable tool to help in wildlife conservation efforts.